2019
DOI: 10.1007/s00259-019-04584-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of standardized 177Lu-PSMA-617 therapy in metastatic prostate cancer patients receiving 7400 MBq every 4 weeks

Abstract: Purpose [ 177 Lu]Lu-PSMA-617 radio-ligand therapy (PSMA-RLT) is emerging in patients with an advanced metastatic castration-resistant prostate cancer (mCRPC). Here, we aimed to estimate the results of PSMA-RLT in terms of response, progression-free survival (PFS), and overall survival (OS) in patients receiving a highly standardized treatment regimen due to mCRPC. The toxicity of PSMA-RLT has also been evaluated. Patients and methods Fifty-four patients (mean age 72 ± 7 years, median PSA at time of initial the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 25 publications
4
48
2
2
Order By: Relevance
“…In their study of 104 patients, Rahbar et al found that there was no incremental benefit to overall survival beyond a PSA decline of 21% [13]. However, Rasul et al noted that there was an added increase in survival, both progression-free and overall, with PSA declines of over 50% and over 80%, though they did not describe the extent [20]. In their prospective study, Hofman et al showed that patients with over 50% PSA decline had longer survival compared to patients with PSA decline of under 50% (17 months vs. 9.9 months) [14].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study of 104 patients, Rahbar et al found that there was no incremental benefit to overall survival beyond a PSA decline of 21% [13]. However, Rasul et al noted that there was an added increase in survival, both progression-free and overall, with PSA declines of over 50% and over 80%, though they did not describe the extent [20]. In their prospective study, Hofman et al showed that patients with over 50% PSA decline had longer survival compared to patients with PSA decline of under 50% (17 months vs. 9.9 months) [14].…”
Section: Reviewmentioning
confidence: 99%
“…The salient features of reviewed studies are summarized in Table 1. With regard to predictors of response to therapy and overall survival, numerous studies have shown that patients with PSA decline in response to RLT experience longer overall survival compared to those who do not respond [12,[17][18][19][20][21][22][23][24][25]. It also appears that the degree of PSA decline correlates with the outcome.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a PSA response of at least 50 % did explain only 9.6 % of respective variation. Following Prostate Cancer Clinical Trial Working Group criteria a PSA decrease surpassing (or equaling) 50 % has been defined in many studies as a biochemically relevant PSA response [2,17,[21][22][23][24], showing in fact a better overall survival [17,[21][22][23]. Against the backdrop of our findings it is important to critically discuss the clinical relevance of an at least 50 % PSA decrease, as its meaningfulness in terms of QoL is rather limited.…”
Section: Discussionmentioning
confidence: 82%
“…Este trabalho revelou que pacientes com maior expressão de PSMA tiveram uma sobrevida maior com relação aos que tinham as menores expressões.Contudo, ainda é incerto concluir se pacientes com baixa expressão de PSMA se beneficiam ou se são prejudicados com o uso de PSMA-617-177 Lu (SEIFERT et al, GBq de PSMA-617-177 Lu a cada 4 semanas reduziu o PSA em 79% dos pacientes, deste grupo 35% apresentaram redução superior a 80%. Após o terceiro ciclo, os principais efeitos adversos foram plaquetopenia e leucopenia.Os autores afirmaram que o aumento de sobrevida global de 119 semanas foi expressivo quando comparado com sobrevida média de 56 semanas nos estudos conduzidos com ciclos administrados a cada 8 semanas(RASUL et al, 2020).O PSMA-617 não tem sido apenas radiomarcado com lutécio-177 ou gálio-68, escândio-44 ou cobre-64 para avaliação in vitro e/ou in vivo. MBq).…”
unclassified